PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI SEKITAR KAWASAN PULAU KAGET KECAMATAN TABUNGANEN KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Muhammad Maulana; Muhammad Helmi; Fonny Rianawati (Universitas Lambung Mangkurat, 2020)
This research is aimed to identification about society knowledge and attitudeof mangrove forest in Pulau Kaget’s area, society’s attitude toward mangrove forest existence and the factor’s that influential toward society perceptions about mangrove forest existence around Pulau Kaget’s area through interview, Data is analyzed by descriptive qualitative and quantitative. Base on this research result the category ofsociety of knowledge and atittude on mangrove forest in Tabunganen sub district is mediun category still have an enough knowledge about mangrove forest. The result showed by respondent’s knowledge with an average score 10.3. Be sides, the percentage of respondent (47%) belonging to medium category which was able to provide correct answer from seven questions. The attitude of Tabunganen Kecil and Tabunganen Muara society can be called enough, this can be seen from average score of 37, related to mostly of society only finish their primary school, but mostly of respondent support to activities and training related to mangrove forest. While the results of statistical tests show there are three factors that influence respondents’ perceptions toward mangrove forest,thatis: knowledge, atittude, and level of education.Keyword: Perception society;mangrove fores; Knowledge;attitude